2020
DOI: 10.2147/pgpm.s226200
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>CYP2C19</em>*<em>2</em> Polymorphism Is Associated with Impaired Oral Clearance of Gliclazide in Healthy Chinese</p>

Abstract: Background: Previous studies suggest gliclazide is metabolised primarily by CYP2C19 rather than CYP2C9, unlike other sulphonylureas. CYP2C19 *2 and *3 polymorphisms are more common in Asians. Methods: We investigated the effect of CYP2C19 polymorphisms on gliclazide pharmacokinetics in 15 healthy male Chinese subjects after a single 80mg oral dose. Results: In CYP2C19 poor metabolisers (*2/*2, n=4), plasma area-under-the-curve was higher by nearly two-fold compared with intermediate metabolisers (*2 and *3 het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The results of this analysis in real-world settings support our previous pharmacokinetic studies regarding the higher plasma level of gliclazide in CYP2C19 PMs. 19 Here, CYP2C19*2 also had pharmacodynamic effects on short-term HbA1c response and longterm treatment failure in patients receiving SU monotherapy or dual therapy of SU and metformin. Patients who were CYP2C19 PMs were 1.5 times more likely to achieve HbA1c target within 18 months of SU initiation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The results of this analysis in real-world settings support our previous pharmacokinetic studies regarding the higher plasma level of gliclazide in CYP2C19 PMs. 19 Here, CYP2C19*2 also had pharmacodynamic effects on short-term HbA1c response and longterm treatment failure in patients receiving SU monotherapy or dual therapy of SU and metformin. Patients who were CYP2C19 PMs were 1.5 times more likely to achieve HbA1c target within 18 months of SU initiation.…”
Section: Discussionmentioning
confidence: 89%
“…18 In a pharmacokinetic study of healthy Chinese subjects, we showed that CYP2C19*2/*2 was associated with 2-fold increase in total plasma gliclazide area-under-the-curve and plasma half-life with 50% reduction in oral drug clearance compared with CYP2C19 EMs. 19 Despite the common use of SUs in Asians, there are no largescale pharmacogenetic studies examining the effect of CYP2C19*2 or CYP2C19*3 polymorphisms on SU treatment response or risk of hypoglycemia in this population. We therefore investigated the associations of CYP2C19 loss-of-function polymorphisms with SU treatment failure, SU efficacy, and risk of hypoglycemia among incident SU users.…”
mentioning
confidence: 99%
“…In many studies, most CYP2C19 mutations involved three common alleles in the Chinese Han population, namely CYP2C19 *2,*3, and *17 ( Chow et al., 2019 ). The current study was conducted on the Henan Chinese Han patient population, and the allele frequencies for CYP2C19 *2,*3, and *17 were found to be 30.8%, 3.8%, and 1.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, microsomes were prepared from six human livers which were not genotyped for CYP2C19 polymorphisms. Furthermore, later in vivo studies showed that gliclazide PK is affected mainly by CYP2C19 polymorphisms [ 11 , 12 , 55 ]. Based on these PK clinical studies in individuals with different CYP2C19 and CYP2C9 genotypes [ 11 , 12 ], it was estimated that the contribution of CYP2C9 to gliclazide metabolism is around 24%, and of CYP2C19 around 76% [ 36 ].…”
Section: Discussionmentioning
confidence: 99%